2007
DOI: 10.1371/journal.pmed.0040003
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Function of Research Ethics Committees in Africa: A Case Study

Abstract: Kass and colleagues explore the strengths and weaknesses of research ethics committees in Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 25 publications
1
105
0
4
Order By: Relevance
“…Budgetary constraints, lack of training, expertise and lack of full time administrators have also been highlighted as major challenges to African RECs [7][8][9][10][11][12][13]. The findings of this survey revealed that the use of modern review technologies, can positively address the communication, storage, security and confidentiality issues as well as, cushion the RECs limited budgets by reducing their operational costs such as telephone, photocopying and protocol distribution costs.…”
Section: Discussionmentioning
confidence: 99%
“…Budgetary constraints, lack of training, expertise and lack of full time administrators have also been highlighted as major challenges to African RECs [7][8][9][10][11][12][13]. The findings of this survey revealed that the use of modern review technologies, can positively address the communication, storage, security and confidentiality issues as well as, cushion the RECs limited budgets by reducing their operational costs such as telephone, photocopying and protocol distribution costs.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of these findings on temporal trends in approval timelines needs to be done with caution considering that approval timelines may be affected by many factors at play in different countries at different time points that may explain the observation that there was no significant difference in approval time by year of submission. These factors include: financial and human resources available to review boards in different countries at different time points [13,14]; capacity building structures of RECs in different countries [7] and complexity of study protocols submitted for ethical and regulatory review. In light of these factors and the fact that the analysis of temporal trends presented by our study and that by Geldenhuys et al [8] does not account for these potentially confounding factors, the interpretation of these findings from the analysis of temporal trends should be done with caution.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Sub-Saharan Africa has an admirable history related to the establishment of RECs and protecting human subjects involved in research activities; several reports suggest that a majority of countries have some procedures in place for ethical reviews. [4,5] We do know from the Kass case study [4] that South Africa (SA) established a REC in 1967 and at least eight other committees had been established since 2002. That said, during this time period and beyond, the African scientific community has been challenged with a variety of ethical issues.…”
Section: Articlementioning
confidence: 99%